2016
DOI: 10.1007/s00726-016-2243-y
|View full text |Cite
|
Sign up to set email alerts
|

NO synthesis from arginine is favored by α-linolenic acid in mice fed a high-fat diet

Abstract: Alterations in NO availability and signaling play a pivotal role at early stages of the metabolic syndrome (MetSynd). We hypothesized that dietary α-linolenic acid (ALA, 18:3 n-3) favors NO availability by modulating amino acid metabolism, with a specific impact on the arginine-NO pathway. Mice were fed a hyperlipidic diet (285 g lipid/kg, 51.1 % energy), rich in either saturated fatty acids (SFA, provided by palm oil, PALM group) or ALA (provided by linseed oil, LIN group). We measured whole-body NO synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…The decrease in BP accompanied by these changes can be attributed to an increase in the level of NO, the strongest endogenous vasodilating agent. The obtained results are consistent with those of experimental studies on mice, where ALA contained in linseed oil increased L-arginine blood levels with minor changes in ADMA [40]. In other studies, conducted in rats, ALA increased NO concentration [23,41].…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in BP accompanied by these changes can be attributed to an increase in the level of NO, the strongest endogenous vasodilating agent. The obtained results are consistent with those of experimental studies on mice, where ALA contained in linseed oil increased L-arginine blood levels with minor changes in ADMA [40]. In other studies, conducted in rats, ALA increased NO concentration [23,41].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we used our mouse model of the early steps of the MetS to explore the effects of dietary plant SL provided by camelina meal in a hypercaloric diet. 41 As expected from this model, after 5 weeks on a hypercaloric diet rich in saturated FA and sucrose (HC-Con group), mice exhibited (as compared to those on a normocaloric diet, NC-group) an increase in body weight and adiposity (Table 2 and Figure 1), and in fasting glycemia (Table 4). After only 3 weeks, these alterations were already detectable and were accompanied by higher values of insulinemia and HOMA-IR index (Table 3), and of glucose and insulin postprandial AUC (Figure 2).…”
Section: ■ Discussionsupporting
confidence: 55%
“…Plant SLs have been shown to exert beneficial effects on some risk factors associated with the MetS, such as altered glucose homeostasis, abnormal lipid profile, and low-grade chronic inflammation. In the present study, we used our mouse model of the early steps of the MetS to explore the effects of dietary plant SL provided by camelina meal in a hypercaloric diet . As expected from this model, after 5 weeks on a hypercaloric diet rich in saturated FA and sucrose (HC-Con group), mice exhibited (as compared to those on a normocaloric diet, NC-group) an increase in body weight and adiposity (Table and Figure ), and in fasting glycemia (Table ).…”
Section: Discussionmentioning
confidence: 87%
“…The specific mechanisms included the regulation of lipid metabolism‐related genes (PPARα, HMGCR, and SREBPs) and inhibition of the expression of inflammatory factors (IL‐6, TNF, MCP‐1, and VCAM‐1) and the activity of NADPH oxidase (Han et al, 2015; Winnik et al, 2011). In addition, ALA (40.74% of the diet) protected the vascular endothelial function of HFD‐induced rats by promoting the production of constitutive NO (Hermier et al, 2016). Kaplan et al (2018) also found that ALA (200 mg/kg) improved the smooth muscle damage of the rat thoracic aorta caused by smoking by inhibiting the expression of COX‐2 and PLA 2 and increasing the expression of eNOS.…”
Section: Pharmacological Effectsmentioning
confidence: 99%